1986
DOI: 10.1128/jcm.24.5.876-878.1986
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Campylobacter spp. isolation in three regions of Ontario, Canada, from 1978 to 1985

Abstract: Isolation rates of Campylobacter spp. were analyzed for an 8-year period, 1978 through 1985. Three laboratories of the Ontario Ministry of Health examined 146,842 human feces samples for bacterial pathogens, including Campylobacterjejuni and Campylobacter coli. Campylobacter spp. were isolated from 5,580 specimens (3.8%), with monthly isolation rates ranging from 1.1 to 7.4%. The data showed a seasQnal distribution of isolations, with peaks during the summer months (June to September). Most infections were in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…3). These figures are 5-15 times the sort of rates reported in industrialized countries (Sibbald & Sharp, 1985;Thompson, Cahoon & Hodge, 1986;Skirrow, 1987) but are not as high as those found in developing countries, e.g. 40% per year (Calva et al 1988).…”
Section: Discussionmentioning
confidence: 73%
“…3). These figures are 5-15 times the sort of rates reported in industrialized countries (Sibbald & Sharp, 1985;Thompson, Cahoon & Hodge, 1986;Skirrow, 1987) but are not as high as those found in developing countries, e.g. 40% per year (Calva et al 1988).…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have provided good support for a hypothesis of increased risk of Campylobacter infection in nonurban settings. Increased incidences of Campylobacter have been noted in rural areas (23,24); in several case-control studies, contact with farm animals (5,7,9) or pets (9-12) was among the risk factors found, and Campylobacter infection has also been associated with small-scale chicken husbandry in rural areas (25,26). In Sweden, an ecologic study on the geography of Campylobacter cases was recently conducted (27).…”
Section: Discussionmentioning
confidence: 99%
“…A summer peak in Campylobacter is consistently reported from temperate countries [1, 2022] often doubling the weekly incidence at the same time each year [22] with later peaks in colder countries [21, 22]. Exceptions include Estonia and Germany with less distinct or repeatable summer peaks [21, 22].…”
Section: Introductionmentioning
confidence: 99%